Antiurolithic activity of Origanum vulgare is mediated through multiple pathways - Khan Aslam; Bashir Samra; Khan Saeed R; Gilani Anwar H (BMC, 2011)
Abstract Background Origanum vulgare Linn has traditionally been used in the treatment of urolithiasis. Therefore, we investigated the crude extract of Origanum vulgare for possible antiurolithic effect, to rationalize its medicinal use. Methods The crude aqueous-methanolic extract of Origanum vulgare (Ov.Cr) was studied using the in vitro and in vivo methods. In the in vitro experiments, supersaturated solution of calcium and oxalate, kidney epithelial cell lines (MDCK) and urinary bladder of rabbits were used, whereas, in the in vivo studies, rat model of urolithiasis was used for the study of preventive and curative effect. Results In the in vitro experiments, Ov.Cr exhibited a concentration-dependent (0.25-4 mg/ml) inhibitory effect on the slope of nucleation and aggregation and also decreased the number of calcium oxalate monohydrate crystals (COM) produced in calcium oxalate metastable solutions. It also showed concentration-dependent antioxidant effect against DPPH free radical and lipid peroxidation induced in rat kidney tissue homogenate. Ov.Cr reduced the cell toxicity using MTT assay and LDH release in renal epithelial cells (MDCK) exposed to oxalate (0.5 mM) and COM (66 μg/cm2) crystals. Ov.Cr relaxed high K+ (80 mM) induced contraction in rabbit urinary bladder strips, and shifted the calcium concentration-response curves (CRCs) towards right with suppression of the maximum response similar to that of verapamil, a standard calcium channel blocker. In male Wistar rats receiving lithogenic treatment comprising of 0.75% ethylene glycol in drinking water given for 3 weeks along with ammonium chloride (NH4Cl) for the first 5 days, Ov.Cr treatment (10-30 mg/kg) prevented as well as reversed toxic changes including loss of body weight, polyurea, crystalluria, oxaluria, raised serum urea and creatinine levels and crystal deposition in kidneys compared to their respective controls. Conclusion These data indicating the antiurolithic activity in Ov.Cr, possibly mediated through inhibition of CaOx crystallization, antioxidant, renal epithelial cell protective and antispasmodic activities, rationalizes its medicinal use in urolithiasis.